LEGAL PROTECTION OF BANK CUSTOMERS IN CYBER CRIME CONNECTED WITH THE INTERNET BANKINGLAW NUMBER 11 OF 2008 CONCERNING INFORMATION AND ELECTRONIC TRANSACTIONS - Risti Dwi Ramasari (International Conference On Law, Business and Governance (ICon-LBG), 2016)
Internet banking allows customers to make payments online. Internet banking is also provided accommodation banking activities through a network of computers anytime and anywhere quickly. The issues in this research are How Legal Protection of Bank Customers in Cyber Crime Against Internet Banking,and how the Internet Banking Agreement Between Banks and Customers. The approach used in this research is normative juridical and juridical empirical. Legal protection for customers by administrative provisions and by the guarantee of deposit insurance. Based Administrative Provisions that explicitly protection or protection gained through the establishment of institutions that guarantee public deposits, and implicitly that protection is generated by the bank supervision and guidance effectively.